IMPLEMENTASI SISTEM MANAJEMEN MUTU BERBASIS NILAI ISLAM DI MAN BIREUEN - Irma Rosita (Jurnal Tarbiyah Almuslim, 2025)
In the context of globalization and educational disruption, Islamic education is expected not only to excel academically but also to be strong in shaping students' character and spiritual values. Therefore, the quality management system implemented at MAN Bireuen is not solely based on administrative and technical standards but also emphasizes core Islamic values such as honesty, responsibility, trustworthiness, and deliberation (shura). This research employs a qualitative approach using a case study method. Data collection techniques include in-depth interviews with the principal, teachers, and education staff, observation of school management activities, and documentation of regulations and quality programs based on Islamic values. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that MAN Bireuen has integrated Islamic values into various aspects of quality management, from planning, implementation, and evaluation to continuous improvement. These values serve as guidelines for decision-making, human resource management, curriculum development, and the cultivation of a work and learning culture. Despite several challenges, such as limited understanding of Islamic quality management concepts among staff and a lack of continuous training, the overall implementation has had a positive impact on school culture, student achievement, and parental and community satisfaction. This study recommends strengthening training in Islamic-based management, continuous monitoring, and the development of an evaluation model that reflects Islamic principles.